1998
DOI: 10.21273/hortsci.33.1.140
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Raspberry Cultivars by Sequence Characterized Amplified Region DNA Analysis

Abstract: Five polymorphic random amplified polymorphic DNA (RAPD) markers for 13 red raspberry (Rubus idaeus L.) and two purple raspberry (R. idaeus L. × R. occidentalis L.) cultivars were cloned and their termini sequenced. Sequence-specific 24-mer primer pairs were synthesized as extended RAPD primers and used in sequence characterized amplified region (SCAR) DNA analysis. All primer pairs generated polymorphic SCAR markers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…These markers were described as potentially codominant. Amplification of several closely sized bands (Type 3 failure) was described for raspberry (Rubus idaeus L. and R. idaeus x R. occidentalis L.) (Parent and Page, 1998) and strawberry (Fragaria L. sp.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These markers were described as potentially codominant. Amplification of several closely sized bands (Type 3 failure) was described for raspberry (Rubus idaeus L. and R. idaeus x R. occidentalis L.) (Parent and Page, 1998) and strawberry (Fragaria L. sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Thus, two multiplex reactions were developed that included either four or five primer sets that adequately and reliably separated the cultivars examined. Problems associated with multiplexing have been described by several groups (Amicucci et al, 2000;Henegariu et al, 1997;Parent and Page, 1998). Multiplexing, however, was considered to be critical to our purposes since one goal was to reduce the number of reactions required which would adequately discriminate common cranberry cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is possible to construct very high density DNA marker maps for application in genome research and positional cloning of genes through this method (Monte-Corvo et al, 2000;Russel et al, 1997). Studies on the genetic diversity of Rubus species have been carried out, including species such as R. idaeus (Parent and Fortin 1993, Graham and Mcnicol, 1995, Graham et al 1997 and R. occidentalis (Parent and Page, 1998), as well as Asian species (Amsellem et al 2000). These studies employed AFLP, RAPD (Random Amplified Polymorphic DNA), RFLP (Restriction Fragment Length polymorphism), and SCAR (Sequence Characterized Amplified Region) markers, as well as SSR (Amsellem et al, 2000;Parent and Fortin, 1993, Graham and Mcnicol, 1995, Graham et al 1997Parent and Page, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The RAPD is a useful and powerful technique for various polymorphism analyses including genetic diversity, identification of cultivars and phylogenetic analysis of many plant species [Khanuja et al 2000, Besnard et al 2001, Lisek and Rozpara 2010, Okoń et al 2014, Gawroński et al 2017. Some studies using RAPD markers in Rubus have also been reported [Parent et al 1993, Graham et al 1994, Graham and McNicol 1995, Graham et al 1997, Parent and Page 1998, Antonius-Klemola 1999, Badjakov et al 2006, Stafne et al 2003, Patamsyte et al 2010, Umar et al 2010. SSR loci are highly polymorphic co-dominant markers also useful for studying the genetic diversity and genetic fingerprinting of many species.…”
mentioning
confidence: 99%